Prevalence of Obesity and Its Association with Socioeconomic Factors in Elderly Iranians from Razavi-Khorasan Province - Mohsen Nematy; Ali Sakhdari; Parnian Ahmadi-Moghaddam; Maliheh Aliabadi; M. Kimiagar; A. A. Ilaty; M. Azimi-Nezhad; M. T. Shakeri; M. Ghayour-Mobarhan; A. Sahebkar; G. Ferns (The Scientific World Journal)
There are few data regarding the prevalence of obesity and its socioeconomic determinants among elderly individuals, particularly in Iran. We wished to determine the prevalence of overweight and obesity in free-living elderly people and the relationship to nutritional and socioeconomic factors in the Razavi-Khorasan province of Iran. Free-living elderly persons (917 males/1045 females), aged ?60 years, were recruited using cluster sampling. Overweight and obesity were evaluated using body mass index (BMI) and subjects were categorized as thin (BMI <18.5 kg/m2), normal (18.5–24.9 kg/m2), overweight (25–29.9 kg/m2), and obese (?30 kg/m2). The association between the prevalence of overweight or obesity with socioeconomic and demographic factors, including gender, place of residence, literacy, type of living, source of income, use of supplements during the past 3 months, and employment status, was examined using regression analysis. The distribution of BMI values indicated that 13, 46.5, 28.9, and 11.7% of the total population were thin, normal, overweight, and obese, respectively. The prevalence of central obesity was higher among Iranian women than men (63.1 vs. 18.6%, respectively). Regression analysis results indicated that gender (p < 0.001), place of residence (p < 0.001), literacy (p = 0.01), and source of income (p < 0.001) were significantly associated with the incidence of overweight or obesity. This study showed that 40.6% of elderly subjects were overweight or obese. Results reinforce the need to plan strategies for primary prevention of this fast-growing public health problem.